Distinct Hepatic Macrophage Populations in Lean and Obese Mice - Mayoral Monibas, Rafael; Johnson, Andrew M. F.; Osborn, Olivia; Traves, Paqui G.; Mahata, Sushil K. (Frontiers in Endocrinology, 2016)
Obesity is a complex metabolic disorder associated with the development of non-communicable diseases such as cirrhosis, nonalcoholic fatty liver disease (NAFLD) and type 2 diabetes (T2D). In humans and rodents, obesity promotes hepatic steatosis and inflammation, which leads to increased production of pro-inflammatory cytokines and acute-phase proteins. Liver macrophages (resident as well as recruited) play a significant role in hepatic inflammation and insulin resistance (IR). Interestingly, depletion of hepatic macrophages protects against the development of high-fat-induced steatosis, inflammation and IR. Kupffer cells (KCs), liver resident macrophages, are the first-line defense against invading pathogens, clear toxic or immunogenic molecules and help to maintain the liver in a tolerogenic immune environment. During high fat diet (HFD) feeding and steatosis, there is an increased number of recruited hepatic macrophages (RHMs) in the liver and activation of KCs to a more inflammatory or M1 state. In this review we will focus on the role of liver macrophages (KCs and RHMs) during obesity.